Gaya Hidup dan Fenomena Perilaku Konsumen pada Warung Kopi di Malang - Ompusunggu, Marthin Pangihutan; Djawahir, Achmad Helmy (Jurnal Aplikasi Manajemen, 2014)
The purpose of this research is to understands and know the description of lifestyle and consumer behaviour phenomenom in a coffeeshops Malang. The consumer behaviour phenomenom is always doing a activites in coffeeshop such as discussion, interaction, and even meeting. Consumers are able to feel relaxed in a coffeeshop atmosphere because they not restricted by a regulations or rules. Activites in a coffeeshop is a reflection of the needs that important to consumers, because encouragement of lifestyle. Type of this research is a qualitative research based on phenomenology, which takes informant from consumer and entrepreneur coffeeshop. The number of informant on this research are 7 informant. Interview, observation, and documentation as an instrument for primary data collection. Method of data collection methodes using interview is done, then the data analysis through manual qualitative analysis is the primary tool analysis on this research.